Studies in Ancient Persia and the Achaemenid Period - Curtis, John (James Clarke & Co, 2020)
Cover -- Book Title -- Copyright -- Table of Content -- Editor's note -- Introduction -- Terence Mitchell's Published Works -- 1 Five Unpublished Persepolis Relief Fragments in the Ashmolean Museum (Paul Collins) -- 2 Where Did the Persian Kings Live in Babylon? (John Curtis) -- 3 The Use of Seals in Babylonia under the Achaemenids (C.B.F. Walker) -- 4 An Iranian in the Court of King Nebuchadnezzar (Alan Millard) -- 5 Biblical Archaeology in the Persian Period (T.C. Mitchell) -- 6 The Textual Connections between the Cyrus Cylinder and the Bible,with Particular Reference to Isaiah (Shahrokh Razmjou) -- 7 Interpreting Sasanian Beards:Significant Images in an Interconnected World (P.O. Harper) -- 8 Sasanian-Zoroastrian Intellectual Lifein the Fifth and Sixth Centuries AD (Mahnaz Moazami) -- Back Cover.